PENGARUH PERBEDAAN BASIS CMC-NA DAN PGA PADA PASTA GIGI EKSTRAK DAUN BIDURI (Calotropis gigantea L.) TERHADAP MUTU FISIK DAN AKTIVITAS ANTIBAKTERI Streptococcus mutans - Tri Prasongko, Erfan; Eka Rahmawati, Azhariana; Resvaty, Ananda Intan Dwi (FACULTY OF PHARMACY, INSTITUT ILMU KESEHATAN BHAKTI WIYATA, 2025)
Background: Toothpaste is a semi-solid preparation used to clean teeth and maintain oral health. Innovations in utilizing natural ingredients, such as Biduri leaf extract (Calotropis gigantea L.), in toothpaste formulation are based on its content of active compounds like flavonoids, tannins, and saponins, which have potential antibacterial properties and thus are beneficial for maintaining dental cleanliness and health. Objective: This study aims to determine the effect of different bases, CMC-Na and PGA, in Biduri leaf extract (Calotropis gigantea L.) toothpaste on its physical quality and antibacterial activity against Streptococcus mutans. Methods:Toothpaste was formulated into two preparations: Formulation 1 (3% CMC-Na base) and Formulation 2 (20% PGA base). Physical quality evaluations included organoleptic testing, pH, homogeneity, and foam height, while stability testing was conducted using the cycling test method. The data were analyzed using Independent T-Test and Paired T-Test. Results: There were significant differences in the physical quality of Biduri leaf extract toothpaste between the CMC-Na and PGA bases in terms of pH and foam height (p<0.05), but no differences in organoleptic properties and homogeneity. In the stability test, both bases were unstable in terms of pH and foam height. Antibacterial activity testing against Streptococcus mutans showed no significant difference between the two bases (p>0.05). Conclusion: The difference between CMC-Na and PGA bases in Biduri leaf extract (Calotropis gigantea L.) toothpaste affects its physical quality and stability, but does not influence its antibacterial activity against Streptococcus mutans.